194k views
20 votes
Solve 2(9-x) = 3 ( x +16 )

2 Answers

7 votes

Answer: x=-6

Explanation:

Let's solve your equation step-by-step.

2(9−x)=3(x+16)

Step 1: Simplify both sides of the equation by distribution


2(9-x)=3(x+16)\\(2)(9)+(2)(-x)=(3)(x)+(3)(16)\\18+-2x=3x+48\\-2x+18=3x+48\\

Step 2: Subtract 3x from both sides.


-2x+18-3x=3x+48-3x\\-5x+18=48

Step 3: Subtract 18 from both sides.


-5x+18-18=48-18\\-5x=30

Step 4: Divide both sides by -5.


(-5x)/(-5) =(30)/(-5) \\x=-6

User Douglas Mesquita
by
4.8k points
8 votes
  • 2(9-x)=3(x+16)
  • 18-2x=3x+48
  • 3x+2x=18-48
  • 5x=-30
  • x=-6
User Tim Ludwinski
by
4.6k points